ASSESSING SERUM ESTROGEN LEVELS AS A POTENTIAL MARKER OF CHRONIC LIVER DISEASE SEVERITY IN MALE PATIENTS: A HOSPITAL-BASED OBSERVATIONAL STUDY IN PAKISTAN - Ayesha Laraib-Ijaz; Noor ul Huda; Jamal afzal; Shaheer Ahmad Dar; Kashif khan; Sadeed Ahmed Darain; Fatima Shams; Aqsa Siddique; Farman Iqbal; Waqas Gohar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction Chronic liver disease (CLD) is a significant public health issue in Pakistan, leading to high morbidity and mortality. Hormonal dysregulation, including alterations in estrogen metabolism due to impaired hepatic clearance, is a well-documented consequence of CLD. Estrogen, primarily known for its reproductive functions, has been implicated in liver disease progression, but its role as a biomarker of liver disease severity remains underexplored. This study aimed to evaluate the relationship between serum estrogen levels and the severity of CLD, as assessed by the Child-Turcotte-Pugh (CTP) score, and to investigate its association with various complications of the Chronic liver disease. Methods This prospective observational study was conducted in the Department of Medicine at a tertiary care hospital in Pakistan from January 2020 to March 2021. Patients diagnosed with CLD were evaluated for demographic characteristics, clinical history, and examination findings. Disease severity was classified using the CTP scoring system. Serum estrogen levels were measured using an electrochemiluminescence assay. Statistical analyses, including the Chi-square test, Kruskal-Wallis test, and independent sample t-tests, were used to assess associations between estrogen levels, disease severity, and complications. A p-value of <0.05 was considered statistically significant. Results The study included 135 patients with a mean age of 49.1 ± 11.2 years. Males comprised 82.2% of the cohort (male-to-female ratio: 4.6:1). The leading causes of CLD were hepatitis C virus infection (n=67, 49.6%), alcohol-related liver disease (n=32, 23.7%), and metabolic dysfunction-associated steatohepatitis (n=15, 11.1%). The mean serum estrogen level was 62.8 ± 14.6 pg/mL (range: 35 to 89 pg/mL), and the mean CTP score was 9.42 ± 2.05. Most patients were classified as CTP Class B (n=59, 43.7%), followed by Class C (n=51, 37.8%) and Class A (n=25, 18.5%).Serum estrogen levels showed a significant positive correlation with CTP scores (R = 0.412, p < 0.001), serum bilirubin (R = 0.361, p < 0.001), and international normalized ratio (R = 0.295, p = 0.002), along with a significant negative correlation with serum albumin (R = -0.419, p < 0.001). The Kruskal-Wallis test demonstrated a strong association between elevated estrogen levels and the severity of ascites (p < 0.001) as well as hepatic encephalopathy (p < 0.001). Using receiver operating characteristic analysis, an estrogen level cut-off > 65 pg/mL predicted severe CLD (CTP Class C) with 79.4% sensitivity and 81.2% specificity. Elevated estrogen levels were found in 74.8% of patients (n=101) with esophageal varices, 85.6% (n=36) with upper gastrointestinal bleeding, 89.7% (n=44) with hepatic encephalopathy, and 77.9% (n=74) with moderate-to-severe ascites. The overall mortality rate was 4.4% (n=6), and deceased patients had significantly higher estrogen levels compared to survivors (p < 0.001). Conclusion Serum estrogen levels demonstrate a strong correlation with CLD severity as determined by the CTP scoring system. The findings suggest that estrogen could serve as a valuable biomarker for assessing disease progression and predicting complications in CLD patients. Given its non-invasive nature and significant prognostic value, serum estrogen measurement may aid in risk stratification and clinical decision-making for patients with CLD.